2020
DOI: 10.5811/westjem.2020.7.48574
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Enclosure for Endotracheal Intubation in a Simulated COVID-19 Scenario: A Crossover Study

Abstract: Introduction Barrier enclosures have been developed to reduce the risk of COVID-19 transmission to healthcare providers during intubation, but little is known about their impact on procedure performance. We sought to determine whether a barrier enclosure delays time to successful intubation by experienced airway operators. Methods We conducted a crossover simulation study at a tertiary academic hospital. Participants watched a four-minute video, practiced one simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In this study, teams of trained airway practitioners using an aerosol box showed increased time to intubation, but no difference in time to LMA insertion or first-pass success rates (for ETI and LMA insertion) compared with teams without an aerosol box. While prior manikin-based studies report slightly longer time to intubation with aerosol box use, certain study design elements such as a single airway practitioner or a lack of prior aerosol box training may have contributed to delayed intubation times. Data from studies assessing intubation in real patients is mixed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this study, teams of trained airway practitioners using an aerosol box showed increased time to intubation, but no difference in time to LMA insertion or first-pass success rates (for ETI and LMA insertion) compared with teams without an aerosol box. While prior manikin-based studies report slightly longer time to intubation with aerosol box use, certain study design elements such as a single airway practitioner or a lack of prior aerosol box training may have contributed to delayed intubation times. Data from studies assessing intubation in real patients is mixed.…”
Section: Discussionmentioning
confidence: 93%
“…Two prospective trials showed no difference in time to intubation or first-pass success rate with aerosol box use, but a survey of practitioners who had used an aerosol box during intubation reported only a 78.9% first-pass success rate . Aerosol box use during intubation requires an increased number of optimization procedures and hand movements, along with hindering visibility for some practitioners . In theory, practicing in pairs should provide sufficient opportunity to overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the setting of the COVID-19 pandemic, the need has arisen to emphasize personal protective equipment and barriers for AGPs [ [16] , [17] , [18] , [19] ]. This is particularly salient for SLPs who must perform FEES to assess the swallowing ability of COVID patients.…”
Section: Discussionmentioning
confidence: 99%